A SARS-CoV-2 Delta variant containing mutation in the probe binding region used for RT-qPCR test in Japan exhibited atypical PCR amplification and might induce false negative result. Issue 5 (May 2022) - Rajib, Samiul Alam; Ogi, Yasuhiro; Hossain, Md Belal; Ikeda, Terumasa; Tanaka, Eiichi; Kawaguchi, Tatsuya; Satou, Yorifumi
Abstract: Introduction: A recent pandemic of SARS-CoV-2 infection has caused severe health problems and substantially restricted social and economic activities. RT-qPCR plays a vital role in the diagnosis of SARS-CoV-2 infection. The N protein-coding region is widely analyzed in RT-qPCR to diagnose SARS-CoV-2 infection in Japan. We recently encountered two cases of SARS-CoV-2-positive specimens showing atypical amplification curves in the RT-qPCR. Methods: We performed whole-genome sequencing of 63 samples (2 showing aberrant RT-qPCR curve and 61 samples infected with SARS-CoV-2 simultaneously in the same area) followed by Phylogenetic tree analysis. Results: We found that the viruses showing abnormal RT-qPCR curves were Delta-type variants of SARS-CoV-2 with a single nucleotide mutation in the probe-binding site. There were no other cases with the same mutation, indicating that the variant had not spread in the area. After searching the database, hundreds of variants were reported globally, and one in Japan contained the same mutation. Phylogenetic analysis showed that the variant was very close to other Delta variants endemic in Japan but quite far from the variants containing the same mutation reported from outside Japan, suggesting sporadic generation of mutant in some domestic areas. Conclusions: These findings propose two key points: i) mutations in the region used for SARS-CoV-2 RT-qPCR can cause abnormal amplification curves, and ii) various mutations can be generated sporadically and unpredictably; therefore, efficient and robust screening systems are needed to promptly monitor the emergence of de novo variants.